### x^2+-5:2x-3:2=0

This solution deals with adding, subtracting & finding the least common multiple.

Bạn đang xem: 5:2x

## Step by Step Solution ## Step 1 :

3 Simplify — 2Equation at the end of step 1 : 5 3 ((x2) - (— • x)) - — = 0 2 2

## Step 2 :

5 Simplify — 2Equation at the kết thúc of step 2 : 5 3 ((x2) - (— • x)) - — = 0 2 2

## Step 3 :

Rewriting the whole as an Equivalent Fraction :3.1Subtracting a fraction from a whole Rewrite the whole as a fraction using 2 as the denominator :

x2 x2 • 2 x2 = —— = —————— 1 2 Equivalent fraction : The fraction thus generated looks different but has the same value as the whole Common denominator : The equivalent fraction and the other fraction involved in the calculation mô tả the same denominator

Adding fractions that have a common denominator :3.2 Adding up the two equivalent fractions địa chỉ cửa hàng the two equivalent fractions which now have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lớn lowest terms if possible:

x2 • 2 - (5x) 2x2 - 5x ————————————— = ———————— 2 2 Equation at the over of step 3 : (2x2 - 5x) 3 —————————— - — = 0 2 2

## Step 5 :

Pulling out lượt thích terms :5.1 Pull out like factors:2x2 - 5x=x•(2x - 5)

Adding fractions which have a common denominator :5.2 Adding fractions which have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lớn lowest terms if possible:

x • (2x-5) - (3) 2x2 - 5x - 3 ———————————————— = ———————————— 2 2 Trying lớn factor by splitting the middle term5.3Factoring 2x2 - 5x - 3 The first term is, 2x2 its coefficient is 2.The middle term is, -5x its coefficient is -5.The last term, "the constant", is -3Step-1 : Multiply the coefficient of the first term by the constant 2•-3=-6Step-2 : Find two factors of -6 whose sum equals the coefficient of the middle term, which is -5.

 -6 + 1 = -5 That"s it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step2above, -6 and 12x2 - 6x+1x - 3Step-4 : địa chỉ up the first 2 terms, pulling out like factors:2x•(x-3) showroom up the last 2 terms, pulling out common factors:1•(x-3) Step-5:Add up the four terms of step4:(2x+1)•(x-3)Which is the desired factorization

Equation at the end of step 5 : (x - 3) • (2x + 1) —————————————————— = 0 2

## Step 6 :

When a fraction equals zero :6.1 When a fraction equals zero ...Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.Here"s how:

(x-3)•(2x+1) ———————————— • 2 = 0 • 2 2 Now, on the left hand side, the 2 cancels out the denominator, while, on the right hand side, zero times anything is still zero.The equation now takes the shape:(x-3) • (2x+1)=0

Theory - Roots of a sản phẩm :6.2 A sản phẩm of several terms equals zero.When a sản phẩm of two or more terms equals zero, then at least one of the terms must be zero.We shall now solve each term = 0 separatelyIn other words, we are going to solve as many equations as there are terms in the productAny solution of term = 0 solves sản phẩm = 0 as well.

Solving a Single Variable Equation:6.3Solve:x-3 = 0Add 3 to lớn both sides of the equation:x = 3

Solving a Single Variable Equation:6.4Solve:2x+1 = 0Subtract 1 from both sides of the equation:2x = -1 Divide both sides of the equation by 2:x = -1/2 = -0.500

### Supplement : Solving Quadratic Equation Directly

Solving 2x2-5x-3 = 0 directly Earlier we factored this polynomial by splitting the middle term. Let us now solve the equation by Completing The Square và by using the Quadratic Formula

Parabola, Finding the Vertex:7.1Find the Vertex ofy = 2x2-5x-3Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up và accordingly has a lowest point (AKA absolute minimum).We know this even before plotting "y" because the coefficient of the first term,2, is positive (greater than zero).Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.Parabolas can mã sản phẩm many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to lớn be able to find the coordinates of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is given by -B/(2A). In our case the x coordinate is 1.2500Plugging into the parabola formula 1.2500 for x we can calculate the y-coordinate:y = 2.0 * 1.25 * 1.25 - 5.0 * 1.25 - 3.0 or y = -6.125

Parabola, Graphing Vertex and X-Intercepts :Root plot for : y = 2x2-5x-3 Axis of Symmetry (dashed) x= 1.25 Vertex at x,y = 1.25,-6.12 x-Intercepts (Roots) : Root 1 at x,y = -0.50, 0.00 Root 2 at x,y = 3.00, 0.00

Solve Quadratic Equation by Completing The Square

7.2Solving2x2-5x-3 = 0 by Completing The Square.Divide both sides of the equation by 2 khổng lồ have 1 as the coefficient of the first term :x2-(5/2)x-(3/2) = 0Add 3/2 to both side of the equation : x2-(5/2)x = 3/2Now the clever bit: Take the coefficient of x, which is 5/2, divide by two, giving 5/4, and finally square it giving 25/16Add 25/16 to lớn both sides of the equation :On the right hand side we have:3/2+25/16The common denominator of the two fractions is 16Adding (24/16)+(25/16) gives 49/16So adding to both sides we finally get:x2-(5/2)x+(25/16) = 49/16Adding 25/16 has completed the left hand side into a perfect square :x2-(5/2)x+(25/16)=(x-(5/4))•(x-(5/4))=(x-(5/4))2 Things which are equal khổng lồ the same thing are also equal lớn one another. Sincex2-(5/2)x+(25/16) = 49/16 andx2-(5/2)x+(25/16) = (x-(5/4))2 then, according khổng lồ the law of transitivity,(x-(5/4))2 = 49/16We"ll refer lớn this Equation as Eq.

Xem thêm: Soạn Văn Bài: Thực Hành Về Thành Ngữ Điển Cố, Soạn Bài Thực Hành Về Thành Ngữ, Điển Cố

#7.2.1 The Square Root Principle says that When two things are equal, their square roots are equal.Note that the square root of(x-(5/4))2 is(x-(5/4))2/2=(x-(5/4))1=x-(5/4)Now, applying the Square Root Principle to Eq.#7.2.1 we get:x-(5/4)= √ 49/16 showroom 5/4 to both sides to obtain:x = 5/4 + √ 49/16 Since a square root has two values, one positive and the other negativex2 - (5/2)x - (3/2) = 0has two solutions:x = 5/4 + √ 49/16 orx = 5/4 - √ 49/16 lưu ý that √ 49/16 can be written as√49 / √16which is 7 / 4